Penerapan Metode ODOS (One Day One Surat) dan Juziyah dalam Menguatkan Hafalan Al Qur'an - Syaifudin, Muhamad (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Applying the right method is one of the main keys in good and contextual learning, especially in memorizing the Qur'an. Sometimes there are several obstacles that make students difficult, bored and lazy in memorizing the Qur'an. The purpose of this research is to describe the application of the ODOS (One Day One Surat) and Juz'iyah methods in strengthening memorization of the Qur'an and to find out the obstacles to the application of the ODOS (One Day One Surat) and Juz'iyah methods in strengthening memorization. Al Qur'an students of SMP Muhammadiyah 3 Cawas Klaten. The type of research used is descriptive qualitative. The research subjects are school principals, tahfidz teachers and students, while the research location is at SMP Muhammadiyah 3 Cawas. Data collection was obtained from interview techniques and documentation in the field. Data analysis uses data reduction, data presentation and conclusion. And the technique of guaranteeing the validity of the data is done by using source triangulation techniques. The results of the study show that 1) The application of the ODOS (One Day One Surat) and Juziyah methods at SMP Muhammadiyah 3 Cawas is quite good because students are used to repeating their memorization, and students can also deposit their memorization in one majlis, even though there are things which needs to be evaluated. 2) Constraints and obstacles in the application of the ODOS (One Day One Letter) and Juziyah methods at Muhammadiyah 3 Cawas Middle School in the form of external constraints and internal constraints, external constraints in the form of learning resources, learning facilities and teacher abilities related to teaching tajwid science which are considered good even though they are not yet state everything and for internal constraints in the form of students' potential abilities and student learning methods which are still different.